2023
DOI: 10.1093/bjd/ljad063
|View full text |Cite
|
Sign up to set email alerts
|

Microblading-transmitted Monkeypox (mpox) infection: fomites matter

Abstract: Microblading is an increasingly popular semi-permanent tattooing technique used for eyebrow pigmentation, involving the use of needles. During the mpox 2022 outbreak in Spain, a 47 -year-old woman with no relevant medical history presented with a 10-day facial skin eruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Five case reports (Akoh et al 2021, Castaño-Fernández & Grau-Pérez 2023, Marcelino et al 2021, Sano et al 2021, Soltany et al 2023) reported microbiological complications in the context of semi-permanent make-up, which included both viral and bacterial infections. The viral infections reported were monkeypox (mpox) (Castaño-Fernández & Grau-Pérez 2023) and Molluscum contagiosum (Marcelino et al 2021) and the bacterial infections reported were orbital cellulitis (Soltany et al 2023), three cases of periorbital cellulitis (Akoh et al 2021, Soltany et al 2023, Sano et al 2021) and necrotising fasciitis (Soltany et al 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five case reports (Akoh et al 2021, Castaño-Fernández & Grau-Pérez 2023, Marcelino et al 2021, Sano et al 2021, Soltany et al 2023) reported microbiological complications in the context of semi-permanent make-up, which included both viral and bacterial infections. The viral infections reported were monkeypox (mpox) (Castaño-Fernández & Grau-Pérez 2023) and Molluscum contagiosum (Marcelino et al 2021) and the bacterial infections reported were orbital cellulitis (Soltany et al 2023), three cases of periorbital cellulitis (Akoh et al 2021, Soltany et al 2023, Sano et al 2021) and necrotising fasciitis (Soltany et al 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Three case reports earned a score of six out of eight (Sano et al 2021, Tierney & Kavanagh 2021, Valbuena et al 2017). Three case reports were rated five out of eight (Bashinskaya et al 2022, Castaño-Fernández & Grau-Pérez 2023, Vera et al 2018). Finally, a single case report was rated four out of eight (Bombonato et al 2015).…”
Section: Resultsmentioning
confidence: 99%